The human sperm basal body is a complex centrosome important for embryo preimplantation development. (28th September 2021) - Amargant, Farners; Pujol, Aïda; Ferrer-Vaquer, Anna; Durban, Mercè; Martínez, Meritxell; Vassena, Rita; Vernos, Isabelle
Abstract: The mechanism of conversion of the human sperm basal body to a centrosome after fertilization, and its role in supporting human early embryogenesis, has not been directly addressed so far. Using proteomics and immunofluorescence studies, we show here that the human zygote inherits a basal body enriched with centrosomal proteins from the sperm, establishing the first functional centrosome of the new organism. Injection of human sperm tails containing the basal body into human oocytes followed by parthenogenetic activation, showed that the centrosome contributes to the robustness of the early cell divisions, increasing the probability of parthenotes reaching the compaction stage. In the absence of the sperm-derived centrosome, pericentriolar material (PCM) components stored in the oocyte can form de novo structures after genome activation, suggesting a tight PCM expression control in zygotes. Our results reveal that the sperm basal body is a complex organelle which converts to a centrosome after fertilization, ensuring the early steps of embryogenesis and successful compaction. However, more experiments are needed to elucidate the exact molecular mechanisms of centrosome inheritance in humans.